Factors Associated With Esophagus Cancers in Togo, Sub-Saharan Africa - Tchin Darré; Toukilnan Djiwa; Roland-Moise Lidawu Kogoe; Kodjo Eugene Eklu; Fousseni Alassani; Panakinao Simgban; Mayi Bombone; Bagassam Sama; Boyodi Tchangai; Aklesso Bagny; Gado Napo-Koura (SAGE Publishing, 2023)
Background: Esophagus cancer is cancer of poor prognosis, of often late diagnosis. The objective of this study was to describe the factors associated with esophagus cancers in the Togolese population. Methods: It was a retrospective descriptive, cross-sectional study, on esophagus cancers histologically diagnosed at the Pathological Laboratory of Lomé over a period of 31 years (1990-2021). Results: We have collected 144 cases of esophagus cancer. The average age of patients was 57 ± 12 years, and the sex ratio was 2.34. The most applicant service was the service of Hepato Gastroenterology of CHU Campus (30.6%). Alcohol (57.6%), tobacco (45.8%) were the most present risk factors. Biopsies were the most addressed (97.2%). The average duration of symptom evolution was 6.42 months and the main symptom at the time of diagnosis was dysphagia (36.8%). The location of cancer was the lower third for 71.5% of cases. At histology, epidermoid carcinoma was the dominant type (90.3%). Male sex was statistically associated with the occurrence of epidermoid carcinoma and female sex with the occurrence of adenocarcinoma ( P  < .001). Alcohol, smoking, and consumption of hot foods were statistically associated with the occurrence of epidermoid carcinoma in this study ( P  < .05). Conclusion: Esophagus cancer remains a serious condition for late diagnosis. These are mainly epidermoid carcinomas and having alcohol and tobacco as risk factors. The awareness of the population on the main risk factors would reduce the incidence of oesophagus cancers within the Togolese population.